2008
DOI: 10.1002/jctb.2095
|View full text |Cite
|
Sign up to set email alerts
|

Semibatch and continuous fructooligosaccharides production by Aspergillus sp. N74 in a mechanically agitated airlift reactor

Abstract: BACKGROUND: Fructooligosaccharides are important sweeteners produced by sucrose biotransformation. Although fructooligosccharides production has been reported widely, most studies have been carried out at laboratory level. This study evaluates semibatch and continuous fructooligosaccharides production by Aspergillus sp. N74 at bench scale in a mechanically agitated airlift.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
3
7
0
Order By: Relevance
“…Ritsema et al (2006) proposed that this motif could influence the entry of the acceptor sucrose when fructose is retained in the enzyme. In that sense, fungal FTases have a "chimeric" domain that supports the findings of invertase activity in fungal FTases under certain conditions (Yun, 1996;Sangeetha et al, 2005;Sanchez et al, 2008aSanchez et al, , 2008bCaicedo et al, 2009). The analysis of this motif in fungi FTases supports our hypothesis that they were generated from an ancestral dicot invertase since they have the "chimeric" (F-and S-type) domain.…”
Section: Single Amino Acids Responsible For Specific Characteristicssupporting
confidence: 78%
See 1 more Smart Citation
“…Ritsema et al (2006) proposed that this motif could influence the entry of the acceptor sucrose when fructose is retained in the enzyme. In that sense, fungal FTases have a "chimeric" domain that supports the findings of invertase activity in fungal FTases under certain conditions (Yun, 1996;Sangeetha et al, 2005;Sanchez et al, 2008aSanchez et al, , 2008bCaicedo et al, 2009). The analysis of this motif in fungi FTases supports our hypothesis that they were generated from an ancestral dicot invertase since they have the "chimeric" (F-and S-type) domain.…”
Section: Single Amino Acids Responsible For Specific Characteristicssupporting
confidence: 78%
“…During the last years, we have worked in the production of FOS by using an A. oryzae strain (Sanchez et al, 2008a(Sanchez et al, , 2008bCaicedo et al, 2009), and recently the ftase gene from that strain was cloned and the tertiary structure of the enzyme was modeled (Rodriguez et al, 2010). To continue the understanding and optimization of FOS production, in this study we conducted a computational analysis of reported sequences for FTases from a diverse source of organisms, such as plants, fungi and bacteria.…”
Section: Introductionmentioning
confidence: 98%
“…FTase produces FOS from sucrose by transferring one to three molecules of fructose. Several microorganisms have FTase, such as Fusarium sp., Aspergillus sp., Aureobasidium sp., Penicillium sp., Arthrobacter sp., Zymomonas mobilis , Bacillus macerans , Candida, Kluyveromyces , and Saccharomyces cerevisia e [41,44,45,46,47,48]. Among these microorganisms, Aspergillus niger and Aureobasidium pullulans are mostly used in the industry [49].…”
Section: Production Of Prebioticsmentioning
confidence: 99%
“…After conducting the enzymatic reaction, the dry weight biomass was determined for both, small and bioreactor scales. This biomass was washed with 50 mM phosphate buffer (pH 5.5) and dried for 48 h at 105 ℃ (Caicedo et al., 2009).…”
Section: Methodsmentioning
confidence: 99%
“…These authors determined the optimal pH (5.5), temperature (60 ℃) and sucrose concentration (>55% w / v ) for FOS production using A. oryzae N74 whole cells. In addition, FOS production at continuous, semibatch and batch operation in an agitated airlift reactor was evaluated, obtaining FOS production yields that ranged from 47.8% to 66.4% depending on the biomass concentration and operational mode (Caicedo et al., 2009; Sánchez et al., 2008). Recently, it was cloned the A. oryzae N74 ftase gene as a previous step for the production of the recombinant enzyme in Pichia pastoris (GenBank accession numbers GU145136 and GU145137) (Rodríguez et al., 2011), and the computational analysis of the encoded FTase allowed to classify it in the glycoside hydrolase family GH32 (Alméciga-Díaz et al., 2011).…”
Section: Introductionmentioning
confidence: 99%